The Influence of Self-Concept on Burnout Among Employees of the Department of Population and Civil Registration in Minahasa Regency - Yesa Grasella Cyntha Ratu; Meike Endang Hartati; Veronika Juliet Kamasi (Psikologi Prima, 2025)
Burnout is a condition of prolonged stress that can reduce performance, work motivation, and quality of service, especially among individuals working in public service sectors. This condition highlights the importance of understanding internal factors that guide behavior and determine individual success, namely self-concept. This study aims to determine the effect of self-concept on burnout among employees of the Population and Civil Registration Department in Minahasa Regency. The study employed a quantitative method. The subjects were 40 employees of the Population and Civil Registration Department in Minahasa Regency, selected using a saturated sampling technique. The measurement instruments were Likert-scale questionnaires, consisting of an adopted self-concept scale with 25 valid items (reliability coefficient = 0.888) and an adapted burnout scale with 18 valid items (reliability coefficient = 0.904). The hypothesis was tested using simple linear regression analysis, resulting in the equation Y = 59.139 – 0.345X. The regression analysis showed a significance value of 0.000 < 0.05, indicating that self-concept has a negative effect on burnout by 39.9%. These findings extend previous research by showing that self-concept not only correlates with burnout but also directly influences it. Furthermore, this study provides new insights into the impact of self-concept on burnout among public service employees in the civil administration sector.